Էլեկտրոնային և սոցիալական մամուլը պետական կառավարման համակարգում - Քալանթարյան, Էդգար (YSU Journal of International Affairs, 2017)
Contemporary societies are characterized by information and communication technologies, which become an essential unifying factor for both state and public organizations. The impact of information touches all of society. These days it’s hard to imagine life without the Internet, social communication, social and electronic media. The spread of Internet is faster than ever. The rapid spread of information and communication technologies states the distinct role of electronic and social media which effecting the information governance systems of any country. The introduction of the Internet and new information technologies in the system of state governance of the Republic of Armenia is a testament to the need to modernize the existing system in order to improve management efficiency.
Keywords: social media, electronic media, effective government, network governance, internet, information, manipulation, social networks, information technologies